THE INFLUENCE OF WORKLOAD, WORK ENVIRONMENT AND MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. BANK RAKYAT INDONESIA TEBING TINGGI BRANCH OFFICE - Dewi Rucci Manulang; Abdul Rahim Matondang; Iskandarini (RADJA PUBLIKA, 2023)
Human resources have a very important role in various sectors, because human resources are a key factor in driving other resources within the company. The importance of the role of human resources has resulted in an organization having to allocate a sizable amount of funds to improve the performance of these human resources. Along with the rapid development of science and technology, quality human resources are demanded. This is because human resources have an important role in advancing the company.